Independent colonization of multiple urban centres by a formerly forest specialist bird species - Evans, Karl L; Gaston, Kevin J; Frantz, Alain C; Simeoni, Michelle; Sharp, Stuart P; McGowan, Andrew; Dawson, Deborah A; Walasz, Kazimierz; Partecke, Jesko; Burke, Terry; Hatchwell, Ben J (Proceedings of the Royal Society. B, Biological sciences, 2009)
Urban areas are expanding rapidly, but a few native species have successfully colonized them. The processes underlying such colonization events are poorly understood. Using the blackbird Turdus merula, a former forest specialist that is now one of the most common urban birds in its range, we provide the first assessment of two contrasting urban colonization models. First, that urbanization occurred independently. Second, that following initial urbanization, urban-adapted individuals colonized other urban areas in a leapfrog manner. Previous analyses of spatial patterns in the timing of blackbird urbanization, and experimental introductions of urban and rural blackbirds to uncolonized cities, suggest that the leapfrog model is likely to apply. We found that, across the western Palaearctic, urban blackbird populations contain less genetic diversity than rural ones, urban populations are more strongly differentiated from each other than from rural populations and assignment tests support a rural source population for most urban individuals. In combination, these results provide much stronger support for the independent urbanization model than the leapfrog one. If the former model predominates, colonization of multiple urban centres will be particularly difficult when urbanization requires genetic adaptations, having implications for urban species diversity.